(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the ways of forming secular and religious worldviews among youth in the context of New Uzbekistan. The study analyzes the role of spiritual and moral education, national values, tolerance, and enlightenment in shaping the ideological consciousness of young people. Particular attention is given to the interaction between secular principles and religious values in the educational process, as well as the importance of protecting youth from destructive ideologies through intellectual and cultural development. The research also highlights the role of educational institutions, family, and social environment in fostering a balanced worldview among the younger generation.